Dendrimer confined Pt nanoparticles: electro-catalytic activity towards the oxygen reduction reaction and its application in polymer electrolyte membrane fuel cells. Issue 92 (8th October 2015) - Arunchander, A.; Peera, S. Gouse; Parthiban, V.; Akula, Srinu; Kottakkat, Tintula; Bhat, Santoshkumar D.; Sahu, Akhila Kumar
<x xml:space="preserve">Abstract</x> Pt-DENs have been synthesized and immobilized on ester and anhydride functionalized Vulcan XC-72R. These catalysts are utilized as fuel cell cathodes and significant enhanced performances have been achieved with the Pt loading of 0.2 mg cm−2.